1975
DOI: 10.1007/bf00388377
|View full text |Cite
|
Sign up to set email alerts
|

Filament formation in vitro of a sieve tube protein from Cucurbita maxima and Cucurbita pepo

Abstract: Phloem proteins of the sieve tube exudate from Cucurbita maxima Duch. and Cucurbita pepo L. were investigated as to their filament forming ability in vitro. From the two main proteins (116000 dalton, 30000 dalton) only the 116000 dalton protein was found to form reversibly distinct filaments of 6-7 nm diameter upon removal of SH-protecting agents from the buffer, whereas the 30000 dalton protein was precipitated as amorphous material under these conditions. The protein filaments were similar to the filaments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…The first P-proteins to be analyzed in detail were PP1 and the 24-kDa phloem lectin PP2, which are the main components of C. maxima exudates and are thought to be covalently linked (15). Cucurbits have long served as model plants in phloem research because their large phloem cells are well suited for microscopy and because they bleed profusely after injury, allowing the direct harvest of phloem exudates (51). Electron microscopy revealed the presence of P-protein filaments in C. maxima exudates (52); these filaments were assumed to be composed of PP1, although the ability of the protein to form stable structural components in vivo was debated because of its high turnover rate (53).…”
Section: Distribution Of Seo Genes Reveals the Uniformity Of P-proteinsmentioning
confidence: 99%
“…The first P-proteins to be analyzed in detail were PP1 and the 24-kDa phloem lectin PP2, which are the main components of C. maxima exudates and are thought to be covalently linked (15). Cucurbits have long served as model plants in phloem research because their large phloem cells are well suited for microscopy and because they bleed profusely after injury, allowing the direct harvest of phloem exudates (51). Electron microscopy revealed the presence of P-protein filaments in C. maxima exudates (52); these filaments were assumed to be composed of PP1, although the ability of the protein to form stable structural components in vivo was debated because of its high turnover rate (53).…”
Section: Distribution Of Seo Genes Reveals the Uniformity Of P-proteinsmentioning
confidence: 99%
“…In Cucurbita spp., two predominant P-proteins, the phloem filament protein or phloem protein 1 (PP1) and the phloem lectin or phloem protein 2 (PP2), have been associated with the structural P-protein filaments (Cronshaw and Sabnis, 1990). In vitro studies have shown PP1 to be the primary structural protein capable of forming P-protein filaments (Kleinig et al, 1975), and PP2, a dimeric poly-GlcNAc-binding lectin, to be covalently linked to the filaments by disulfide bridges (Read and Northcote, 1983). The expression of PP1 and PP2 is developmentally related to defined stages of phloem differentiation .…”
mentioning
confidence: 99%
“…In Cucurbita two phloem-specific proteins, termed PP1 and PP2, account for most of the exudate protein (19). It has been proposed that one or both proteins form the P-protein filaments seen in sieve elements by electron microscopy (13,19). Although the proteins have similar amino acid compositions (19,26,27), they differ in mol wt and other properties: PP1 has a…”
mentioning
confidence: 99%
“…molecule (20), and forms filaments upon oxidation (13). PP2 is a dimer of 48,000 Mr with six cysteine residues (20), and is a lectin (1,23).…”
mentioning
confidence: 99%